2019
DOI: 10.15547/bjvm.2019
|View full text |Cite
|
Sign up to set email alerts
|

Protein and lipid species in seminal plasma of fertile Holstein-Friesian bulls

Abstract: Protein and lipid molecules in seminal plasma (SP) collected from fertile bulls were investigated. Semen was collected from 10 bulls (2 ejaculates each) and examined for standard semen analysis. Raw SP was recovered by centrifugation and total protein (TP) concentration was determined using a refractometer. Raw SP was desalted using a Sephadex G-25 desalting column then both raw and desalted SP was subjected to SDS-PAGE. Neutral lipids and phospholipids of raw and desalted SP were separated by thin-layer chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
0
0
0
Order By: Relevance
“…This method has been widely used with the basic principle of separating proteins based on molecular weight (MW). SP proteins of 15 and 22–24 kDa were known to correlate with fertility [ 19 ]. Kumar et al [ 20 ] reported that a 22 kDa protein was known as beta nerve growth factor, which is related to the ovulation induction factor.…”
Section: Introductionmentioning
confidence: 99%
“…This method has been widely used with the basic principle of separating proteins based on molecular weight (MW). SP proteins of 15 and 22–24 kDa were known to correlate with fertility [ 19 ]. Kumar et al [ 20 ] reported that a 22 kDa protein was known as beta nerve growth factor, which is related to the ovulation induction factor.…”
Section: Introductionmentioning
confidence: 99%